Bearing defect diagnosis and acoustic emission. - Morhain, A.; Mba, David (Professional Engineering Publishing, 2003)
Acoustic emission (AE) was originally developed for non-destructive testing of static structures, however, over the years its application has been extended to health monitoring of rotating machines and bearings. It offers the advantage of earlier defect detection in comparison to vibration analysis. However, limitations in the successful application of AE technique for monitoring bearings have been partly due to thedifficulty in processing, interpreting and classifying the acquired data. The investigation reported in this paper was centered on the application of standard acoustic emissions (AE) characteristic parameters on a radially loaded bearing. An experimental test-rig was modified such that defects could be seeded onto the inner and outer races of a test bearing. As the test-rig was adapted for this purpose it offered high background acoustic emission noise providing a realistic test for fault diagnosis. In addition to a review of current diagnostic methods for applying AE to bearing diagnosis, the results of this investigation validated the use of r.m.s, amplitude, energy and AE counts for diagnosis. Furthermore, this study determined the most appropriate threshold level for AE count diagnosis, the first known attempt.